Essence and types of modernization theory (Journal of Philosophy Culture and Political Science, 2018)
In the XX century. especially popular are thetheory of  modernization. Initially usingthis theory described processes thatoccurred in western europe in a new andrecent time, in the period of transition from agrariansociety to industrial. Whereinmodernization was a processcovering different sides of lifesociety: from economy to culture